Pengelolaan Prioritas Belanja Dana Desa Abung Kabupaten Hulu Sungai Tengah - Jepriansyah Jepriansyah; Muhammad Saleh (PPJP Universitas Lambung Mangkurat, 2023)
This research aims to see the criteria for determining village fund spending in Abung Village and how the priority of Abung Village fund spending is Hulu Sungai Tengah Regency. Respondents in this study were six people who influenced the determination of village funds. This study uses the Analytical Hierarchy Process method. So the results obtained in this study are alternative criteria for the Village Potential RPJMDes and Village Problems influencing spending priorities. This shows the alternative criteria for selecting priority expenditure priorities for Village development, Village development empowerment 37.28%, Village development 36.80%, community development 18.92%, and Village administration 7%. It can be concluded that the most dominant in the research that has been done is Empowerment of Village Community Development worth 37,28%